How to Sustainably Feed a Microbe: Strategies for Biological Production of Carbon-Based Commodities with Renewable Electricity - Butler, Caitlyn S.; Lovley, Derek R. (Frontiers in Microbiology, 2016)
As interest and application of renewable energy grows, strategies are needed to align the asynchronous supply and demand. Microbial metabolisms are a potentially sustainable mechanism for transforming renewable electrical energy into biocommodities that are easily stored and transported. Acetogens and methanogens can reduce carbon dioxide to organic products including methane, acetic acid, and ethanol. The library of biocommodities is expanded when engineered metabolisms of acetogens are included. Typically, electrochemical systems are employed to integrate renewable energy sources with biological systems for production of carbon-based commodities. Within these systems, there are three prevailing mechanisms for delivering electrons to microorganisms for the conversion of carbon dioxide to reduce organic compounds: 1) electrons can be delivered to microorganisms via H2 produced separately in a electrolyzer, 2) H2 produced at a cathode can convey electrons to microorganisms supported on the cathode surface and 3) a cathode can directly feed electrons to microorganisms. Each of these strategies has advantages and disadvantages that must be considered in designing full-scale processes. This review considers the evolving understanding of each of these approaches and the state of design for advancing these strategies towards viability.